2008
DOI: 10.1002/mus.21009
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐sectional area reference values for nerve ultrasonography

Abstract: Ultrasound allows for a non-invasive structural assessment of nerves, muscles, and surrounding tissues, and therefore it is increasingly being used as a supplement to traditional electrodiagnostic studies. As investigators have begun to use ultrasound to explore peripheral nerves, it has become clear that conditions such as entrapment, hereditary neuropathies, acquired neuropathies, trauma, and nerve tumors result in an increase in nerve cross-sectional area. Reference values have not been published for the cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

53
300
14
16

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 283 publications
(383 citation statements)
references
References 16 publications
53
300
14
16
Order By: Relevance
“…Similarly to our results, Heinemeyer et al found no correlation between nerve size parameters and age, height and body weight, but reported thicker nerves on the upper limbs in males [15]. Cartwright et al [16] reported that nerve size correlated with body weight and body mass index, and that these correlations were most pronounced in the nerves of the proximal leg. They also found that females had smaller nerves than males.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Similarly to our results, Heinemeyer et al found no correlation between nerve size parameters and age, height and body weight, but reported thicker nerves on the upper limbs in males [15]. Cartwright et al [16] reported that nerve size correlated with body weight and body mass index, and that these correlations were most pronounced in the nerves of the proximal leg. They also found that females had smaller nerves than males.…”
Section: Discussionsupporting
confidence: 90%
“…However, we did not measure femoral and sciatic nerves, which are considerably larger, with CSA as high as 41 mm 2 in case of the sciatic nerve [25]. Table 4 also shows that CSA values across these studies are consistent for the major upper limb nerves, with the exception of the radial nerve in the spiral groove reported by Cartwright et al [16]. However, in the most recent study of Won et al [17] and in previous studies reporting reference values for the radial nerve [8,19] in that the C5 root is the smallest among the cervical roots.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…To correlate our results with in vivo studies we reviewed ultrasound and MRI data from sciatic and sural nerves in healthy controls (Table 3). 9,16,23,26,42,44 These studies also demonstrate a large variability with regard to CSA, especially of the sural nerve. 9,15,16,26,44 Specifically, the sural nerve CSA as measured by ultrasound ranged from 1.44 to 5.3 mm 2 .…”
Section: Discussionmentioning
confidence: 62%
“…Several recent articles focus on the use of ultrasound in diagnosing or mapping peripheral nerve injuries 11 . Even in animal studies the correlation between anatomical measurements and ultrasound measurements have been established.…”
Section: Resultsmentioning
confidence: 99%